Elliptically birefringent chemically tuned liquid crystalline nanocellulose composites for photonic applications - Singh, Shiva; Bhardwaj, Shakshi; Verma, Chhavi; Chhajed, Monika; Balayan, Kajal; Ghosh, Kaushik; Maji, Pradip K. (Journal of Molecular Liquids, 2022)
Cellulose nanocrystals (CNCs) based photonic materials are one of the promising materials in the recent trends. The liquid crystalline behavior of the CNCs can be tailored to different advanced applications. The proposed research investigates the potential of CNCs as an optically active material. CNCs were tuned to hydroxypropyl nano cellulose (HPNC) with the degree of substitution 1.39. The prepared liquid crystalline HPNC were dispersed in various concentrations of monomethyl ether of polyethylene glycol to get waterborne materials with specific optical anisotropy. The extraction, modification, and morphology of the CNCs were investigated using NMR (Nuclear Magnetic Resonance), TEM (Transmission Electron Microscopy), XRD (X-ray Powder Diffraction), and FESEM (Field Emission Scanning Electron Microscopy) analysis. The prepared HPNC was analyzed using a hot stage POM (Polarized Optical Microscope) for optical anisotropy. The thermal stability of prepared CNCs and HPNC was also investigated. Upon optimization using rheology and POM, it was found that at the ratio of 1:1, HPNC (5 wt%) and mPEG (40 wt%) had the most distinct optical properties. The potential of the prepared materials can be further explored in sensing, smart coating, and security materials. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: bagasse; Cellulose nanocrystals; Elliptical birefringence; liquid crystals; optical anisotropy